2021
DOI: 10.3390/ma14071621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Working Distances between Sandblasting Device and Composite Substrate Surface on the Repair Bond Strength

Abstract: This study investigates the effect of defined working distances between the tip of a sandblasting device and a resin composite surface on the composite–composite repair bond strength. Resin composite specimens (Ceram.x Spectra ST (HV); Dentsply Sirona, Konstanz, Germany) were aged by thermal cycling (5000 cycles, 5–55 °C) and one week of water storage. Mechanical surface conditioning of the substrate surfaces was performed by sandblasting with aluminum oxide particles (50 µm, 3 bar, 10 s) from varying working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The sample sizes varied between 5 [43] to 61[30] in each study. The aging methods included liquid storage (water [3, 9, 27, 44, 45] and saliva [46]), thermocycling [20, 22-25, 29, 31, 32, 42, 47], or a combination of the two [21, 26, 28, 30, 43, 48]. Seven studies [22-25, 30, 43, 46] provided micro-tensile bond strength, four [3, 9, 44, 47] indicated micro-shear bond strength, ten [20, 21, 26-29, 31, 32, 42, 48] gave shear bond strength, and only one [45] evaluated tensile bond strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample sizes varied between 5 [43] to 61[30] in each study. The aging methods included liquid storage (water [3, 9, 27, 44, 45] and saliva [46]), thermocycling [20, 22-25, 29, 31, 32, 42, 47], or a combination of the two [21, 26, 28, 30, 43, 48]. Seven studies [22-25, 30, 43, 46] provided micro-tensile bond strength, four [3, 9, 44, 47] indicated micro-shear bond strength, ten [20, 21, 26-29, 31, 32, 42, 48] gave shear bond strength, and only one [45] evaluated tensile bond strength.…”
Section: Resultsmentioning
confidence: 99%
“…The surface treatment protocols performed on old composite resins also play a significant role in determining the durability of the repair bond. Invitro research findings had also utilized a variety of surface treatment methods, such as roughening with abrasive papers [20][21][22][23], diamond burs [24][25][26], Al 2 O 3 particles [3,22,27], silica coated particles [28][29][30], and lasers [31,32] as mechanical; and numerous bonding mechanisms, adhesives, and salinization as chemical surface treatments [3,22,23,27], solely or in combination to overcome the bonding obstacles. The main objective of such surface modifications is to produce a strong bond through the micromechanical interlocking between fresh and old composite resins.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Several studies have evaluated the effectiveness of this method. [29][30][31] However, air abrasion can activate the formation of cracks and surface damage and compromise the core mechanical characteristics. Therefore, it is recommended to use small particles with a diameter between 30 and 50 µm, moderate pressure (2.5 bar), for 10 sec and at 10 mm from the target as performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the observed µTBS values in this study, SEM images showed an irregular topography pattern after surface treatment using 53 µm aluminum oxide. Structural changes, such as the destruction of both the resin matrix and filler particles, may lead to a better micromechanical interlocking between the substrate and repair RBC after surface treatment with aluminum oxide particles [36]. Aluminum oxide as the standard abrasive powder for use in air-abrasion has a Mohs hardness index of 9, which is strong enough to remove the contaminated superficial layer of RBC via the non-selective destruction of the RBC compartments (see Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 99%